Asociación entre diámetro y altura total en plantas de Cedrelinga cateniformis (Ducke) Ducke y en plantas de Osteophloeum platyspermum (A. DC.) Warb. En bosque natural. Puerto Almendra, Loreto, Perú - 2021 - Paima Ríos, Leopoldo Dante (Universidad Nacional de la Amazonía Peruana, 2023)
The investigation was carried out at the CIEFOR Puerto Almendra – FCF - UNAP facilities, San Juan Bautista district, Maynas province, Loreto region. The objective was to determine the degree of association between diameter and total height in plants of Cedrelinga cateniformis (Ducke) Ducke "tornillo" and Osteophloeum platyspermum (A. DC.) Warb. “cumala blanca” in natural forest. Puerto Almendra, Loreto, Peru- 2021. The variables used were the diameter and total height of the species under study; sample 1 presented Class 1 (10cm < 20 cm) with 10 individuals; class 2 (20cm < 30cm) with 5 individuals; class 3 (30 < 40cm) with 5 individuals; class 4 (40cm < 50cm) with 5 individuals and class 5 (? 50cm) with 5 individuals; in total there were 30 individuals; for sample 2 the individuals were chosen randomly. The results indicate that there is a good to excellent relationship between diameter - total height for both species; the allometric S-Curve and logarithmic models had a better fit for the diameter-total height relationship in the species Osteophloeum platyspermum (A. DC.) Warb. “cumala blanca” and for the species Cedrelinga cateniformis (Ducke) Ducke “tornillo” were S – Curved and cubic.

La investigación se ejecutó en las Instalaciones del CIEFOR Puerto Almendra – FCF - UNAP, distrito de San Juan Bautista, provincia Maynas, región Loreto. El objetivo fue determinar el grado de asociación entre el diámetro y altura total en plantas de Cedrelinga cateniformis (Ducke) Ducke “tornillo” y de Osteophloeum platyspermum (A. DC.) Warb. “cumala blanca” en bosque natural. Puerto Almendra, Loreto, Perú- 2021. Las variables utilizadas fueron el diámetro y altura total de las especies en estudio; la muestra 1 presentó Clase 1 (10cm < 20 cm) con 10 individuos; clase 2 (20cm < 30cm) con 5 individuos; clase 3 (30 < 40cm) con 5 individuos; clase 4 (40cm < 50cm) con 5 individuos y clase 5 (? 50cm) con 5 individuos; en total fueron 30 individuos; para la muestra 2 los individuos fueron elegidos al azar. Los resultados indican que existe de buena a excelente relación entre diámetro – altura total para ambas especies; los modelos alométrico S – Curva y logarítmica tuvieron mejor ajuste para la relación diámetro – altura total en la especie Osteophloeum platyspermum (A. DC.) Warb. “cumala blanca” y para la especie Cedrelinga cateniformis (Ducke) Ducke “tornillo” fueron S – Curva y cúbico.
Keywords: Inventario forestal; Alometría; Altura; Diámetro; Tornillo; Cedrelinga cateniformis; Cumala blanca; Osteophloeum platyspermum; https://purl.org/pe-repo/ocde/ford#4.01.02